Adjacent Joint Restriction Differentially Influences Intra- and Inter-rater Reliability and Agreement of Goniometric Measurements - Brendan L. Pinto; Tatjana Stankovic; David M. Frost; Tyson A. C. Beach (North American Sports Medicine Institute, 2022)
# Background Reliability and agreement of goniometric measurements can be altered by variations in measurement technique such as restricting adjacent joints to influence bi-articular muscles. It is unknown if the influence of adjacent joint restriction is consistent across different range of motion (ROM) tests, as this has yet to be assessed within a single study. Additionally, between-study comparisons are challenged by differences between methodology, participants and raters, obscuring the development of a conceptual understanding of the extent to which adjacent joint restriction can influence goniometric ROM measurements. # Purpose To quantify intra- and inter-rater reliability and levels of agreement of goniometric measurements across five ROM tests, with and without adjacent joint restriction. # Study Design Descriptive reliability study # Methods Three trained and experienced raters made two measurements of bilateral ankle dorsiflexion, first metatarsophalangeal dorsiflexion, hip extension, hip flexion, and shoulder flexion, with and without adjacent joint restriction. Intraclass correlation coefficient (ICC), standard error of measurement (SEM), along with participant, measurement/rater and random error variance were estimated. # Results Eleven females (age 21.4 ±2.3 years) and 19 males (age 22.1 ±2.8 years) participated. Adjacent joint restriction did not influence the reliability and agreement in a consistent way across the five ROM tests. Changes in the inter-rater reliability and agreement were more pronounced compared to the intra-rater reliability and agreement. Assessing variance components (participant, measurement/rater and random error variance) that are used to calculate the ICC and SEM, improved interpretation of ICC and SEM scores. # Conclusion The effects of adjacent joint restriction on reliability and agreement of goniometric measurements depend on the ROM test and should be considered when comparing measurements between multiple raters. Reporting variance components that are used to calculate the ICC and SEM can improve interpretation and may improve between-study comparisons, towards developing a conceptual framework to guide goniometric measurement technique. # Level of Evidence 3b